2017
DOI: 10.1634/theoncologist.2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Targeted Deep Sequencing in Solid-Cancer Patients and Utility for Biomarker-Selected Clinical Trials

Abstract: This study demonstrated that the panel-based sequencing program resulted in an increased rate of trial enrollment of metastatic cancer patients into biomarker-selected clinical trials. Given the expanding list of biomarker-selected trials, the guidance percentage to matched trials is anticipated to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…A recent study evaluating a South Korean population from the Samsung Medical Center reported that a total of 55 of 418 (12.0%) patients harbored a biomarker that led to subsequent rational allocation to a clinical trial. 11 The most commonly mutated oncogenes in the overall cohort included KRAS (19%), PIK3CA (16%), EGFR (5%), BRAF (3%) and KIT (3%) aberrations, while the most frequently mutated tumor suppressor genes included TP53 (40%), which again parallels other precision oncology studies. The expected higher prevalence of EGFR aberrations in Asian patients with lung cancer was confirmed in the IMAC study Specifically, 15 of 48 (31%) lung tumors harbored at least one mutation in the EGFR domain.…”
Section: How Does the Imac Study Compare To Other Precision Oncology supporting
confidence: 71%
See 1 more Smart Citation
“…A recent study evaluating a South Korean population from the Samsung Medical Center reported that a total of 55 of 418 (12.0%) patients harbored a biomarker that led to subsequent rational allocation to a clinical trial. 11 The most commonly mutated oncogenes in the overall cohort included KRAS (19%), PIK3CA (16%), EGFR (5%), BRAF (3%) and KIT (3%) aberrations, while the most frequently mutated tumor suppressor genes included TP53 (40%), which again parallels other precision oncology studies. The expected higher prevalence of EGFR aberrations in Asian patients with lung cancer was confirmed in the IMAC study Specifically, 15 of 48 (31%) lung tumors harbored at least one mutation in the EGFR domain.…”
Section: How Does the Imac Study Compare To Other Precision Oncology supporting
confidence: 71%
“…This 8% patient match rate is similar to the 5–11% match rates reported in other studies. A recent study evaluating a South Korean population from the Samsung Medical Center reported that a total of 55 of 418 (12.0%) patients harbored a biomarker that led to subsequent rational allocation to a clinical trial . The most commonly mutated oncogenes in the overall cohort included KRAS (19%), PIK3CA (16%), EGFR (5%), BRAF (3%) and KIT (3%) aberrations, while the most frequently mutated tumor suppressor genes included TP53 (40%), which again parallels other precision oncology studies.…”
Section: How Does the Imac Study Compare To Other Precision Oncology supporting
confidence: 55%
“…To our knowledge, this is the first and largest study to use an umbrella platform trial design with preplanned genomic biomarker analyses to assign patients with advanced gastric cancer to molecularly matched therapies. Using a centrally standardized molecular screening protocol, we enrolled 772 patients with gastric cancer and successfully performed tissue analysis for more than 90% (92.6%) of the patients as reported in our previous studies (28,31). In this study, we demonstrated that when comprehensive molecular screening is linked to seamless immediate access to parallel matched trials, nearly 1 in 7 (14.7%) patients with advanced gastric cancer can receive biomarker-assigned drug treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Genomic variations are increasingly being utilized as reliable biomarkers for predicting clinical response to therapy for gastric cancer (27)(28)(29). To identify genomic variants that significantly correlate with clinical response, we compared the maximal tumor burden change per RECIST 1.1 against single genomic alterations ( Fig.…”
Section: Prediction Of Best Clinical Response Based On Genomic Variatmentioning
confidence: 99%
See 1 more Smart Citation